Revisiting Gryposuchus jessei Gürich, 1912 (Crocodylia: Gavialoidea): specimen description and comments on the genus - Souza, Rafael Gomes De; Riff, Douglas; de Souza-Filho, Jonas P.; Kellner, Alexander W. A. (Zootaxa, 2018)
Gryposuchus Gürich, 1912 is the most diverse genus within the Gavialoidea. However, the type species G. jessei Gürich, 1912 has been subject of controversy and was regarded conspecific with G. neogaeus (Burmeinster, 1885) or G. colombianus (Langston, 1965). Here we provide a revision of G. jessei to verify the conspecific hypothesis and the implications for the genus Gryposuchus. Our study shows that G. jessei is a valid species, and a new specimen was referred to this taxon. The comparisons with other Gavialoidea species enabled the proposition of three exclusive characters for the genus. We further advocate a sister affinity between G. jessei and G. pachakamue.